An investigation into the long-term carbonation of vegetal concretes containing a viscosity modifying agent. (16th August 2021) - Sheridan, Joseph; Sonebi, Mohammed; Taylor, Su; Amziane, Sofiane
Highlights: Long-term carbonation of vegetal concretes is investigated, with and without VMA. Vegetal concretes were found to carbonate very quickly, especially hemp concretes. Carbonation was found to have no impact on specimen mass or dimensions. Carbonation increased compressive strength of VMA samples vs coetaneous controls. Carbonation inhibited strength development of untreated vs coetaneous controls. Abstract: In modern times issues such as sustainability and carbon footprint have become subjects of significant interest on a global scale. A leading industry in greenhouse emissions is the construction industry, and the industry's carbon footprint needs to be reduced in order to meet emissions targets. Hemp concrete and rapeseed concrete are two alternative sustainable building materials that can help the construction sector improve and meet those targets. Because of their relatively recent introduction, limited studies are available on the durability of these materials. This paper investigates the effect of long-term accelerated carbonation on hemp and rapeseed concretes manufactured with a natural cement and, in some cases, a polyacrylic acid viscosity modifying agent (VMA). Natural carbonation in an outdoor environment was also studied. It was found that the mixes carbonated quickly under accelerated conditions, however no impact on mass or specimen dimensions were observed. In the case of the VMA mixes, it was found that the compressive strength of the samples was improved compared to the equivalently aged control samples. However, it was found that compressive strength was actually inhibited in the untreated mixes when compared with the control samples.